Reflective Learning in Cross-Cultural and Cross-Disciplinary Virtual Classrooms - LUȘTREA, Anca; LUCHEȘ, Daniel; DINCĂ, Melinda (2023)
The Reflective learning in cross-cultural and cross-disciplinary virtualclassrooms was elaborated under the auspices of the project “Bringing Real Lifeinto Virtual Classrooms” (EEA 21-COP-0004), implemented by the WestUniversity of Timisoara, Romania, in partnership with the NorwegianUniversity of Science and Technology, Norway, under the EEA FinancialMechanism 2014-2021.The book presents an analysis of the reflective practice of students whoattended a joint course between UVT and NTNU, which involved experientiallearning in transnational and cross-disciplinary groups of students. Thestudents used digital and VR technologies to learn in a virtual environment.